Exploring perceptions and experiences of the parents of patients: intervention services of a Johannesburg multidisciplinary cleft lip and palate team - Jammine, Georgia Haitas (My University, 2015)
Cleft lip and palate is one of the most common birth defects. The cleft may affect the patient's aesthetic appearance and may result in feeding difficulties, communication impairment as well as psychosocial problems. Management of the disorder is intensive and long-term, and is best handled through early intervention by a multidisciplinary team of professionals. Rationale: In contrast to other developing countries in Africa, in South Africa, there are a number of multidisciplinary cleft lip and palate teams; however there is a lack of research regarding the evaluation of their services. This study sought to evaluate the service of a cleft palate team in the private healthcare sector of Johannesburg, and a combined clinic which it ran. Objective: The purpose of this study was to inform best practice models in cleft palate teamwork by exploring the experiences and perceptions of the parents/caregivers of the patients attending the combined clinic, run by a multidisciplinary cleft palate team in Johannesburg, and described the services it provided. Method: The study incorporated a self-administered questionnaire, which was completed by 33 parents/caregivers, and a review of the patients’ medical records documenting the intervention they had received. Descriptive statistics and content analysis were used to interpret the data. Results: The record review described the time frame and nature of intervention by the various professionals individually, and within the combined clinic. Analysis of the questionnaire revealed the general satisfaction experienced by the parents/caregivers with the service provided, as well as their reservations regarding some aspects of the service. Implications and conclusions: The results indicated that parents/caregivers valued the treatment they received by a multidisciplinary team of expert professionals who met in a combined clinic. Implications emerged that suggested possible improvements to the service as well as recommendations for cleft palate team care in South Africa. The importance of regular evaluation of services and possible tools for conducting them were highlighted.
The discipline of Speech Pathology and Audiology School of Human and Community Development Faculty of Humanities University of the Witwatersrand In fulfilment of the degree of Masters of Arts in Speech Pathology May, 2015